STRATEGIC MANAGEMENT PRACTICES AND THEIR IMPACT ON ORGANIZATIONAL PERFORMANCE: A STUDY OF SMES IN EMERGING MARKETS - Sari, Avid Leonardo (Komitmen: Jurnal Ilmiah Manajemen, 2024)
This study examines the strategic management practices adopted by small and medium-sized enterprises (SMEs) in emerging markets and their impact on organizational performance through a comprehensive literature review. SMEs play a crucial role in economic development, especially in emerging markets, where they drive innovation, employment, and growth. However, their ability to sustain competitive advantage often depends on the effectiveness of their strategic management practices. This research aims to identify the strategic management practices that most significantly influence organizational performance and to analyze the contextual factors that affect their adoption and effectiveness in SMEs within emerging markets. By systematically reviewing existing academic literature, the study synthesizes findings on key practices such as strategic planning, environmental scanning, and adaptive capabilities, highlighting their role in enhancing organizational performance. The review also identifies external factors, such as market volatility, regulatory challenges, and resource limitations, that constrain the effectiveness of these practices. The study provides practical recommendations for SME managers to optimize their strategic management processes and offers insights for policymakers to create supportive environments for SME growth in emerging markets.